Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada Badan Kepegawaian dan Sumber Daya Manusia Kota Tangerang Selatan - Holillah, Siti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The purpose of this research is to determine the influence of work motivation and work discipline on employee performance at the Personnel and Human Resources Agency of South Tangerang City. The method used is quantitative. Sampling technique Using a simple random sampling technique, a sample of 33 employees of the Human Resources Apparatus Competency Development Section was taken. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work motivation has a significant effect on performance with the results of the hypothesis test obtained t count > t table or (3.638 > 1.669). Work Discipline has a significant effect on performance with the hypothesis test value obtained t count > t table or (5.137 > 1,669). Work Motivation and Work Discipline simultaneously have a significant effect on performance with a calculated F value of 57.187 (50.18%) while the remaining 49.82% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (50.18 > 3, 18) With the value of the Coefficient of Determination, the value obtained is 57.18%. With this value, there is a fairly strong influence of work motivation and work discipline on employee performance in civil service agencies and South Tangerang City Human Resources with 46.30% is influenced by other factors that are not included in the testing in this thesis.